Attitudes towards digital citizenship in university students from southern Sonora, Mexico - Jesús Guillermo Rolando Rendón Gil; Joel Angulo Armenta; Carlos Arturo Torres Gastelú (Universidad de Guadalajara, 2023)
This study analyzed the attitudes of university students towards digital citizenship to improve practices when using technologies. The methodological design was mixed with a qualitative phenomenological approach and the quantitative part was correlational-causal with a non-experimental cross-sectional design. 84 students participated, of which 45 were studying engineering and 39 undergraduates. To obtain data, a semi-structured survey was applied individually to 72 participants, a focus group of three key informants and nine in an interview. The findings show that the process of appropriation of digital citizenship in university students still has a long way to go, given the limited acquisition of behaviors inherent to the proper exercise of digital citizenship. In this sense, the results are expressed in two aspects; on the one hand, the positive attitude where technology is expressed as an important part of society and its development, on the other hand, there is the negative attitude that perceives technology as a mere expendable tool. Finally, it is concluded that students must still improve the use of technologies since this use can negatively affect their training process.